Предмет: Алгебра, автор: keksik1kok

Помогите!
Решите уравнение

Приложения:

Ответы

Автор ответа: Юленька194
0
 frac{3}{x-3} - frac{6}{2-x} =6
3(2-x)-6(x-3)=6(x-3)(2-x)
6-3x-6x+18=6(2x-x²-6+3x)
24-9x=6(5x-x²-6)
8-3x=2(5x-x²-6)
8-3x=10x-2x²-12
2x²-3x-10x+12+8=0
2x²-13x+20=0
D= (-13)²-4*2*20= 169 - 160=9
x_1= frac{13+3}{4} = frac{16}{4} =4
x_2= frac{13-3}{4} = frac{10}{4} = frac{5}{2} =2,5

ОДЗ: х≠3, х≠2
Ответ: 2,5 ; 4


Похожие вопросы
Предмет: Қазақ тiлi, автор: aluamajbasova
Предмет: Алгебра, автор: bolodem534